ANALYSIS OF THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, COMPENSATION AND MOTIVATION ON EMPLOYEE INNOVATION PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AS AN INTERVENING - Susilowati, Atik; Kirana, Kusuma Chandra; Subiyanto, Didik (Journal of International Conference Proceedings, 2022)
So that organizational goal can be achived  employee performance is an important think that needs attention. This study aims to analyze the influence of transformational leadership style, compensation and motivation on employee performance by using Organizational Citizenship Behavior (OCB) as an intervening variable. The subjects in this study were educational staff at the Indonesian Institute of the Arts Yogyakarta.  The sample used was 121 respondents. Determination of the number of samples using the Krejcie-Morgan method. This research is a quantitative study. The sampling technique used is a simple random sampling technique. The analysis tool used in this study used Partial Least Square (PLS), namely SEM which is based on variance with SmartPLS software. From the test results, the results were obtained: 1) Transformational Leadership Style affects Innovation Performance; 2) Compensation does not affect innovation performance; 3) Motivation Affects innovation performance; 4) Leadership style affects OCB; 5) Compensation has no Effect on OCB; 6) Motivation affects OCB; 7) OCB Affects Innovation Performance. The advice that can be given is the need to involve educational personnel in the implementation of activities at ISI Yogyakarta which can foster a sense of responsibility in each employee.Keywords: Compensation, Innovation performance, Motivation, OCB, Transformational leadership